Determinants of Crop Diversification amongst Agricultural Co-Operators in Dundwa Agricultural Camp, Choma District, Zambia - Dube, Lighton; Numbwa, Revaux; Guveya, Emmanuel (Asian Journal of Agriculture and Rural Development, 2016)
A sound understanding of the socio-economic characteristics of smallholder farmers and how they influence their crop diversification decisions would help policy makers in crafting appropriate measures for promoting crop diversification. The objectives of this study is to assess the degree of crop diversification and the factors influencing crop diversification among the farm households at Dundwa Agricultural Camp of Zambia. The study uses primary data collected from 60 farm households using structured questionnaire during the period October to November 2014. The degree of crop diversification among farm households was measured using the Entropy index. Further, the censored Tobit model was used to examine how the farmers’ socioeconomic characteristics influences crop diversification. The mean entropy index is 0.88 and this showsa very high degree of crop diversification among the farmers. The Tobit regression model showed that crop diversification is positively influenced by the gender of head of household, the production of cash crops by the household and household investment in basic farming equipment. On contrary, the age of head of household, total farm size, access to agricultural markets and total area cultivated negatively influenced crop diversification. The study recommends for increased capacity building of female headed households in farm decision-making and promoting household investment in basic farming implements as measures to promoting crop diversification.